Serum cystatin C is not an appropriate marker for kidney involvement in patients with primary Sjögren's syndrome. (4th November 2014) - Altunoğlu, Alpaslan; Erten, Şükran; Şahin, Ali; Işıkoğlu, Semra; Neşelioğlu, Salim; Erzurum, Cahide; Erel, Özcan
Abstract: Objectives: We aimed to investigate serum cystatin C (cysC) levels in primary Sjögren's syndrome (pSS) patients, and evaluate its correlation with renal involment. Materials and methods: Eighty‐six pSS patients and 65 age‐ and gender‐matched healthy controls were enrolled into the study. Serum cysC, urea, serum creatinine (SCr), creatinine clearance (CrCl), glomerular filtration rates (GFR), Na, K, Mg, Ca, uric acid, P, erythrocyte sedimentation rate (ESR), C‐reactive protein (CRP), anti‐Ro/SS‐A, anti‐La/SS‐B, antinuclear antibodies, 24‐h urinary poteinuria and microalbuminuria were evaluated. Results: Mean serum cysC levels did not differ between the patients and healthy controls ( P  >   0.05). Nine patients with pSS had proteinuria over 150 mg (and microalbuminuria over 30 mg) per 24 h. In patients with proteinuria, serum cysC levels correlated with serum K ( r  =   0.279, P  =   0.024), ESR ( r  =   0.405, P  =   0.001) and the disease duration ( r  =   0.235, P  =   0.04), respectively. Patients with positive anti‐Ro/SS‐A and anti‐La/SS‐B antibodies had higher SCr levels compared to those with negative serology ( r  =   0.292, P  =   0.009, and r  =   0.259, P  =   0.022, respectively). Nine patients with proteinuria and anti‐Ro/SS‐A, anti‐La/SS‐B positivity tended to have lower K and Mg levels which suggests subclinical renal tubular acidosis. Conclusion: There were no associations between serum cysC levels and renal involvement in patients with pSS. However, in patients with proteinuria, serum cysC levels were correlated with acute‐phase reactants, suggesting an association with disease activity in terms of degree of inflammation.